2021
DOI: 10.1212/wnl.0000000000012246
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes (15 Years) After Subthalamic Nucleus Deep Brain Stimulation in Patients With Parkinson Disease

Abstract: Objective:To evaluate the effects of deep brain stimulation of the subthalamic nucleus (STN-DBS) in Parkinson disease (PD) patients on motor complications beyond 15 years after surgery.Methods:Data about motor complications, quality of life (QoL), activities of daily living, the UPDRS motor scores, dopaminergic treatment, stimulation parameters, and side effects of STN-DBS were retrospectively retrieved and compared between before surgery, at 1 year and beyond 15 years after bilateral STN-DBS.Results:Fifty-one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 40 publications
6
73
2
2
Order By: Relevance
“…One might argue that optimization of DBS parameters should have yielded better results than in our cohort but, over the 12-year period, attempts of adjustments did not provide significant improvement in the remaining patients. This was also reported by others [ 9 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…One might argue that optimization of DBS parameters should have yielded better results than in our cohort but, over the 12-year period, attempts of adjustments did not provide significant improvement in the remaining patients. This was also reported by others [ 9 ].…”
Section: Discussionsupporting
confidence: 90%
“…In a new retrospective analysis of the Grenoble cohort [ 9 ], Bove and colleagues reported a sustained benefit of STN-DBS beyond 15 years in 51 patients, not only on motor function but also on global quality of life (QoL). One explanation for this discrepancy was the much younger age of their patients at the time of surgery (51 ± 8.5 years old), even if the disease duration was similar (11.3 ± 3.8 years) to ours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that hypomania was elicited in ∼30% of patients with PD during the acute stimulation in our study. The prevalence was similar to a recent report that demonstrated the occurrence of impulsive control disorders and psychosis was 47 and 25%, respectively (Bove et al, 2021).…”
Section: Limitations and Further Clinical Applicationssupporting
confidence: 90%
“…Previous studies have suggested that the effects of CSAI on dyskinesia are transient [29,30]. The effects of STN DBS on dyskinesia seem to be significant and last longer [19,31]. AIMS score also evaluates the dyskinesia in Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%